Generalised granuloma annulare in an immunocompetent adult: a rare presentation - Suseela, Bodasingi; Gopal, K. V. T.; Raju, P. V. Krishnam; Sagar, N. K.; Babu, K. Sudhir (International Journal of Research in Dermatology, 2024)
Granuloma annulare (GA) a chronic, non-infectious, granulomatous, necrobiotic disorder of the skin and subcutaneous tissue. We report a rare case of generalized granuloma annulare (GGA) in an immunocompetent individual presented with lesions over trunk and distal extremities. A 62 -year-old male patient came with complaints of reddish raised lesions over trunk, and lower extremities of 10 months duration. The lesions started over the abdomen, progressed over the limbs, associated with mild itching. On dermatological examination, multiple erythematous well marginated papules, coalescing to form infiltrated plaques were seen over abdomen, back, flanks and bilateral calf region. Differential diagnosis of Sarcoidosis, BB/BL Hansens, Cutaneous T cell lymphoma, Lichen Myxedematosus were considered. Slit Skin Smear was negative for AFB. Histopathology showed interstitial distribution of histiocytes and few Langhan’s type giant cells in the superficial dermis. Based on findings, a diagnosis of GGA was made. The patient was treated with emollients, topical steroids, anti- histamines, PUVA sol (8-methoxypsoralen 20 mg/day) and Injection Methotrexate 12.5 mg weekly once for 8 weeks. He is under follow-up. GGA is associated with diabetes mellitus, hyperlipidemia, malignancy, thyroid disease, infections. GGA differs from the localized form by a later age of onset, protracted course with only rare spontaneous resolution, poor response to therapy, and increased prevalence of HLA Bw 35. In the present case even on thorough investigation none of the possible associations could be detected. Our case highlights GGA which is a rare clinical variant in a healthy adult.